x=abs(y+z) x=+(y+z)=y+z x=-(y+z)=-y-z
this is very hard to write out without superscripts so it would be written out like this: y= k times x times cubed root of z if this was all reduced it would be: y=kx(z^1/3 ) i think this is right. >_< i hope this helped!
If x y and y z, which statement is true
It is not easy to illustrate this in a table since it would need to be a 3-d table. The browser which we are required to use is bad enough for ordinary tables. So here goes:X = True, Y = True, Z = True then (X or Y or Z) = TrueX = True, Y = True, Z = False then (X or Y or Z) = TrueX = True, Y = False, Z = True then (X or Y or Z) = TrueX = True, Y = False, Z = False then (X or Y or Z) = TrueX = True, Y = True, Z = True then (X or Y or Z) = TrueX = True, Y = True, Z = False then (X or Y or Z) = TrueX = True, Y = False, Z = True then (X or Y or Z) = TrueX = True, Y = False, Z = False then (X or Y or Z) = FalseThe simple way to remember is that the OR gate gives False only when each input is False.
x + 1 = y y + 3 = z z = y + 3 = (x + 1) + 3 = x + 4 Or: x = y - 1 = (z - 3) - 1 = z - 4 Which results in the same: x exceeds z by 4.
24x2y2z5
x cubed y cubed z squared
y * (x-1) = z Express as x,divide both sides by y(x - 1) = z/yadd 1 on both sidesx = z/y + 1
Answer : 369,254. If you are multiplying X and Y, then subtracting Z. So your formula should look like: (XY) - Z. Where, X = 783, Y = 472, and Z = 322 So that, X times Y is used to subtract Z. You should get 369,254.
Suppose there were x children. Then y = 4*x Therefore x = y/4. Also, z = 4.5*x so that 2*z = 9*x = 9*(y/4) so that 8*z = 9*y or z = 8/9*y
xy + y = z xy = z - y (xy)/y = (z - y)/y x = (z - y)/y
The expression y^4 - z^4 can be factored using the difference of squares formula. It can be written as (y^2 + z^2)(y^2 - z^2), which can be further simplified to (y^2 + z^2)(y + z)(y - z).
It can be, it need not be.
You could say it's "the product of number A and number B squared".For example,Let's call our two unknown numbers y and z.You're asking "what is y*z*z ?"Any number times itself is the number squared, so y*z*z = y*z^2Product means multiply, so y*z^2 is the product of y and z squared.Be careful though, as the sentence could be interpreted as (y*z)^2 rather than y*z^2. Perhaps it's even better to say "the product of y and the square of z".
If x = y and y = z then x = z
x=abs(y+z) x=+(y+z)=y+z x=-(y+z)=-y-z
There are 8 different subsets. The null set. {x} {y} {z} {x y} {x z} {y z} {x y z}